Modelling historical mesocosm data: Application of a fish bioenergetics model in semi‐natural conditions. Issue 4 (27th June 2018) - David, Viviane; Goussen, Benoit; Tebby, Cleo; Joachim, Sandrine; Porcher, Jean‐Marc; Beaudouin, Rémy
Abstract: Developing ecological models for accurately predicting the dynamics of a population and individual physiological processes in field conditions is a challenging task for ecosystem management and ecological risk assessment. Here, we propose to assess the relevance of a dynamic energy budget (DEB) model calibrated using data previously generated from laboratory experiments for adult three‐spined sticklebacks ( Gasterosteus aculeatus ) living in semi‐natural conditions. We compared different ways of integrating different data sets such as temperature and prey abundance obtained in mesocosm experiments to assess the predictive capacity of the model. By this study, we provide recommendations for developing an appropriate environmental scenario (e.g. natural variations of food and temperature) for using a DEB model in a field context. We conclude that a DEB model calibrated with laboratory data can be used to predict the physiological processes of an organism living in semi‐natural conditions, but that the reproductive behaviour of the organism can affect the predictions. At last, we suggest that further studies on the feeding behaviour may be necessary for immature organisms.